The influence of leadership styles on job performance in telecommunication company of Algeria (OTA) - Abdelmoumen, Benchabane (2018)
This study attempts to present a picture of leadership style in Orascom Telecom Algeria (OTA). The primary purpose of this study is to analyse the relationship between transformational, transactional, servant, and participative leadership, and job performance. The study population is comprised of Telecommunications Company in Algeria located in Algiers, Oran. Data were collected from 205 employees. SmartPLS was used in order to determine whether the hypotheses were accepted. The results supported all of the hypotheses of this study, discovered that transformational, transactional, servant, and participative leadership have positive effects on job performance. The results affirmed that transformational leadership, transactional leadership, servant leadership, and participative leadership styles affect job performance of OTA’ employees. It is hoped that the outcome of this study can be used as guidance for OTA Algeria to empower their workforce.